2020
DOI: 10.1002/jsfa.10541
|View full text |Cite
|
Sign up to set email alerts
|

l‐Glutamate stimulates cholecystokinin secretion via the T1R1/T1R3 mediated PLC/TRPM5 transduction pathway

Abstract: BACKGROUND It is known that cholecystokinin (CCK) plays an essential role in reducing food intake and driving weight loss. Previous studies demonstrated that amino acids were capable of triggering CCK release through G protein‐coupled receptors, but the sensing mechanism remains obscure, especially the intracellular signaling pathway. RESULTS l‐Glu, rather than its d‐isomer, robustly stimulated CCK secretion in a porcine duodenal model, and the secretory response was augmented by incubation with the allosteric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…The gut-brain axis is known to play an important role in regulating brain function, and as a result, influences psychological and emotional stability (35,36). L-glutamate, a savory umami taste substance, has the potential to play a role in gut-brain axis communication via activation of taste receptors and subsequent vagus nerve (37)(38)(39)(40). Our previous data in SHR showed that monosodium glutamate (MSG) ingestion successfully decreased strong aggressive behavior in a social interaction test (41).…”
Section: Introductionmentioning
confidence: 99%
“…The gut-brain axis is known to play an important role in regulating brain function, and as a result, influences psychological and emotional stability (35,36). L-glutamate, a savory umami taste substance, has the potential to play a role in gut-brain axis communication via activation of taste receptors and subsequent vagus nerve (37)(38)(39)(40). Our previous data in SHR showed that monosodium glutamate (MSG) ingestion successfully decreased strong aggressive behavior in a social interaction test (41).…”
Section: Introductionmentioning
confidence: 99%